Depressive-Like Behaviors Induced by Chronic Social Defeat Stress Are Associated With HDAC7 Reduction in the Nucleus Accumbens - Qian, Weijun; Yu, Chao; Wang, Shuai; Niu, Aijun; Shi, Guangyan; Cheng, Yuancui; Xu, Ning; Jin, Qiangqiang; Jing, Xu (Frontiers in Psychiatry, 2021)
Persistent symptoms of depression indicate the adaptive involvement of stable molecules in the brain that may be manifested at the level of chromatin remodeling, such as histone acetylation. Former studies have identified alterations in histone acetylation and deacetylation in several animal models about depression. However, the specific histone deacetylases related with depression are needed to be explored. Here, social avoidance behaviors, anxiety- and depression-like behaviors were all found in mice suffered from chronic social defeat stress. Moreover, we also discovered that the amount of the class II histone deacetylase, HDAC7 rather than HDAC2, was significantly decreased in the nucleus accumbens of defeated mice, which suggested that HDAC7 might be a crucial histone deacetylase in a chronic social defeat stress model. Our data showed that the depressive-like behaviors induced by chronic social defeat stress were associated with HDAC7 reduction in nucleus accumbens. HDAC7 might be a promising therapeutic target for depression.